(untitled) (Simbiótica. Revista Eletrônica, 2022)
The article proposes to reflect on the notion of “brand new” movements and collectives from the literature that characterize them as novelty in the face of the use of social networks, the non-party linkage, horizontality and the notion of autonomy of these organizations. We asked if the characteristics of the “brand new” movements and collectives as a novelty and are not similar to other movements and political groups in different historical times. In this way, we will present a brief debate on autonomous movements and the notion of autonomy from events like May 68 in France and Italy to analyze how some of the “brand new” movements and collectives inherited old practices. Keyword: brand new; autonomism; may 1968.